The Minerals–Energy Complex in South Africa: An Empirical Debunking - Reddy, Niall (Development and change, 2025)
A hugely influential framework in South African political economy holds that the country has been dominated for the better part of a century by a Minerals–Energy Complex (MEC) comprising powerful firms and state agencies involved in mining and a range of downstream industries. The MEC is said to act as a ‘system of accumulation’ determining patterns of accumulation across the economy. This article argues that MEC theories rest on hollow empirical foundations. It shows, firstly, that the apparent size, stability and integration of MEC sectors in national accounting data are a statistical artefact of the overly expansive and ad hoc way in which the MEC has been defined. Secondly, it shows that the political‐institutional conditions for an MEC system of accumulation no longer exist, if they ever did. Conglomerates related to MEC sectors once possessed the ability to shape economy‐wide accumulation dynamics, but it is unclear if their interests were ever geared towards the self‐reproduction of core sectors at the expense of diversification. With liberalization those capacities were dismantled. The article closes by showing how assumptions of corporate hegemony — latently embedded in MEC theories — leave us unable to explain major trends in South African political economy such as state capture.